2019
DOI: 10.1039/c9cp03884a
|View full text |Cite
|
Sign up to set email alerts
|

Dendrite nucleation in lithium-conductive ceramics

Abstract: A chemomechanical analysis suggests that bulk lithium plating in polycrystalline LLZO becomes energetically favourable above a critical current. This grain-coating mechanism rationalizes dendrite nucleation without making reference to surface cracks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
65
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 31 publications
(53 reference statements)
1
65
0
Order By: Relevance
“…22 Since we want to understand the impact of the ASR on |Dp| we calculated |Dp| for the cells studied here according to |Dp| ¼ 2pf int (63 bulk CCD) 1/2 , with 3 bulk ¼ 3 rel 3 and 3 rel z 50. 42,44 In contrast to the earlier report, the values obtained range from 5 Â 10 3 Pa to 7 Â 10 5 Pa. The signicantly higher values correspond to higher ASR values.…”
Section: Failure Mechanismmentioning
confidence: 61%
See 1 more Smart Citation
“…22 Since we want to understand the impact of the ASR on |Dp| we calculated |Dp| for the cells studied here according to |Dp| ¼ 2pf int (63 bulk CCD) 1/2 , with 3 bulk ¼ 3 rel 3 and 3 rel z 50. 42,44 In contrast to the earlier report, the values obtained range from 5 Â 10 3 Pa to 7 Â 10 5 Pa. The signicantly higher values correspond to higher ASR values.…”
Section: Failure Mechanismmentioning
confidence: 61%
“…In a very recent experimental paper by Li and Monroe, the authors report about the mechanism of dendrite nucleation. 42 They showed that the stress associated with dendrite growth is about 1 kPa. This value is far below the fracture stress of about |Dp| ¼ 6 MPa for LLZO.…”
Section: Failure Mechanismmentioning
confidence: 99%
“…[72] A precise knowledge of the charge transfer kinetics is very important for the prediction of precise potential profiles in batteries and modeling approaches for lithium metal growth through ceramic electrolytes. [38,49,73] With this work, we hope to stimulate a rethinking of the kinetics of metal electrodes on single ion conductors and to inspire future theoretical and experimental work on the atomistic understanding of the charge transfer reaction. This understanding is required to obtain meaningful predictions of the rate capability of lithium metal anodes under ideal conditions.…”
Section: Discussionmentioning
confidence: 98%
“…For precise theoretical models dealing with the lithium metal anode in SSBs, the charge transfer reaction needs to be well known. [38] In literature, the charge transfer resistance is often set equal to the interfacial impedance. However, recent results clearly show that the Li|LLZO interfacial impedance does not reflect the charge transfer alone, but is rather dominated by current constriction resistances in the ISE at the interface.…”
Section: Introductionmentioning
confidence: 99%
“…For example, numerous works have reported the resistance at GB related to the decrease in the ion conductivity in LLZO, [18][19][20][21] while some other studies have observed contradictory results, where the sample with small grain size has higher conductivity than that containing large-sized grains, indicating the faster ion transport at the GBs. [22][23][24] Moreover, GBs are expected to contribute to the Li dendrite growth in LLZO, [25][26][27] which leads to the short-circuiting of the cell 22,[28][29][30][31] . It is reported that the inhomogeneous depletion 30 and low ion conductivity 32 at the GB are responsible for the dendrite growth.…”
Section: Introductionmentioning
confidence: 99%